Investment in the Building Industry: 1930–1935. Part I - Bowen, Ian (Review of Economic Studies, 1939)
Journal Article Investment in the Building Industry: 1930—1935. Part I Get access Ian Bowen Ian Bowen Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 6, Issue 2, February 1939, Pages 156–160, https://doi.org/10.2307/2967398 Published: 01 February 1939